Effect of ultrasonic irradiations on gas-liquid mass transfer coefficient (kLa); Experiments and modelling - Asgharzadehahmadi, S.; Davoody, M.; Ghotli, R.A.; Abdul Raman, Abdul Aziz; Parthasarathy, R. (Elsevier, 2016)
Sonochemical reactors have proven to be very useful for intensification of various reaction systems. However, there is a lack of understanding in mass transfer mechanism under ultrasonication due to dependency of mass transfer on various parameters. The present work aims at investigating the effect of ultrasonic intensity on volumetric gas-liquid mass transfer coefficient, kLa, as a function of gas flow rate and temperature. Response surface methodology (RSM) coupled with central composite design (CCD) was used for design, statistical analysis and evaluation of the interaction between operational parameters. The maximum value of kLa was found to be 0.0128 s-1 in an optimum range of ultrasonic intensity between 320 and 360 W, though gas flow rate was the most influential parameter for kLa. In the next part of the study, a model was developed based on ANFIS to map the input variables to the outputs. Satisfactory agreement was observed between the ANFIS predictions and experimental data.